2018
DOI: 10.1007/s12274-018-2241-3
|View full text |Cite
|
Sign up to set email alerts
|

Unusual switchable peroxidase-mimicking nanozyme for the determination of proteolytic biomarker

Abstract: Detection of enzyme biomarkers originating from either bio-fluids or contaminating microorganisms is of utmost importance in clinical diagnostics and food safety. Herein, we present a simple, low-cost and easy-to-use sensing approach based on the switchable peroxidase-mimicking activity of plasmonic gold nanoparticles (AuNPs) that can catalyse for the oxidation of 3,3',5'5-tetramethylbenzidine (TMB) for the determination of protease enzyme. The AuNP surface is modified with casein, showing dual functionalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 48 publications
1
45
2
Order By: Relevance
“…Biswas et al found gold nanorods (AuNRs) of 2.8 aspect ratio to possess a catalytic efficiency for 3,3′,5,5′-tetramethylbenzidine (TMB) oxidation slightly higher than cysteamine-capped gold nanospheres (AuNSs) of 34 nm. However, McVey et al [102] observed that smaller AuNSs (14 nm diameter) showed a much higher catalytic efficiency, in agreement with the catalytic model studies previously mentioned. Moreover, these smaller AuNSs have overcome the efficiency of biological enzymes (Fig.…”
Section: Size and Shape Dependencesupporting
confidence: 84%
See 1 more Smart Citation
“…Biswas et al found gold nanorods (AuNRs) of 2.8 aspect ratio to possess a catalytic efficiency for 3,3′,5,5′-tetramethylbenzidine (TMB) oxidation slightly higher than cysteamine-capped gold nanospheres (AuNSs) of 34 nm. However, McVey et al [102] observed that smaller AuNSs (14 nm diameter) showed a much higher catalytic efficiency, in agreement with the catalytic model studies previously mentioned. Moreover, these smaller AuNSs have overcome the efficiency of biological enzymes (Fig.…”
Section: Size and Shape Dependencesupporting
confidence: 84%
“…Most applications encompassed in this category are related to diagnostic tools to detect toxic contaminants in environmental waters. This mainly includes heavy metals [136,[176][177][178][179][180][181][182][183], pesticides [100,184,185] or micro-organisms [102,[186][187][188][189], for being the most common contaminants, but it could potentially include any others. Nonetheless, these are not the only examples of gold nanozyme applications in the environmental sector, especially since their catalytic activities started to be exploited for wastewater treatment to degrade or convert toxic molecules into innocuous products [190,191].…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…1(c), blue triangles). Due to the overlapping of plasmonic peak from AuNP aggregation (~ 650 nm) with the second peak from oxidised TMB (oxTMB), the most prominent peak at 370 nm was selected for analysis [17]. From these results, it is evident that the presence of AuNPs notably enhances the rate of TMB oxidation therefore, confirming the strong peroxidase-mimicking activity of bare-AuNPs.…”
Section: Gold Nanoparticles (Aunps) Exhibit a Strong Peroxidase-like mentioning
confidence: 94%
“…Previously, plasmonic AuNPs have been widely exploited for the colorimetric detection of Hg 2+ through T-Hg 2+ -T co-ordination chemistry [10][11][12] and interactions with molecules such as cysteamine [13], tween-20 [14], papain [15] and thioctic acid [16]. Additionally, AuNPs can mimic the activities of natural enzymes (termed nanozymes), for example horseradish peroxidase (HRP) [17], glucose oxidase [18][19][20], superoxide dismutase [21] and catalase [22], which have been well documented for detecting metal ions, including Pb, Co, K and Hg [23][24][25]. However, some of these mimicking behaviours can exhibit relatively low catalytic activity [26].…”
Section: Introductionmentioning
confidence: 99%
“…We developed the single-step approach for the detection of nanozymes with peroxidase- peroxidase-mimicking activity by shielding the catalytic surface. 31 For lateral flow immunoassay, additional reduction occurs because of the trapping of nanozymes inside membrane pores. 41,42 To overcome the blocking, the surface of nanozymes can be recuperated by overgrowth with a bare catalytic layer over initial particles.…”
Section: Resultsmentioning
confidence: 99%